Teologi Religionum dalam Perspektif Postkolonial Asia: Rekonstruksi Dialog Injili di Indonesia - Daud Darmadi; Royke Lontoh (Sekolah Tinggi Teologi Bethel Ambon, 2026)
This article discusses the reconstruction of theologia religionum from an Asian postcolonial perspective as a foundation for developing a contextual Evangelical dialogue in Indonesia. The study departs from a critique of Western paradigms, exclusivism, inclusivism, and pluralism, which are considered insufficient to fully explain the reality of Asian religious plurality. Using a qualitative-descriptive approach based on library research, this study analyzes the thoughts of several Asian theologians, particularly Aloysius Pieris, C. S. Song, and R. S. Sugirtharajah. The findings reveal that Asian theology of religions is constructed not primarily through philosophical speculation, but through the historical experiences of plural societies, poverty, colonialism, and local cultural struggles. This study proposes a model of “Asian postcolonial Evangelical dialogue” grounded in three main principles: Christocentricity, contextuality, and dialogicality. This model maintains the particularity of Christ without falling into hegemonic exclusivism or syncretistic pluralism. Therefore, this research offers a new conceptual framework for the development of interreligious dialogue in Indonesia that is more contextual, non-hegemonic, and transformative.